(untitled) (Publicaciones en Ciencias y Tecnología, 2009)
In this paper the Smith normal form of certain matrices is used to provide another char acterization for the surjectivity of one-dimensional linear cellular automata with multiple local rules over the ring ZN of integers modulo N ≥ 2.. We reached this goal through an adaptation of a well known result of G. A. Hedlund which characterize the surjectivity of general one-dimensional cellular automata.